2022
DOI: 10.1016/j.mcpro.2022.100200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Profiling of Human Synovial Fluid Suggests Increased Protein Interplay in Early-Osteoarthritis (OA) That Is Lost in Late-Stage OA

Abstract: profiling of human synovial fluid suggests increased protein interplay in early-osteoarthritis (OA) that is lost in late-stage OA, Molecular & Cellular Proteomics (2022), doi: https://doi.org/10.1016/j.mcpro.2022.100200. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 78 publications
2
34
0
Order By: Relevance
“…Ali et al showed in their study an overall higher protein expression in early-stage OA and a reduced response in late-stage OA [ 13 ].…”
Section: Synovial Fluid Physiopathologymentioning
confidence: 99%
See 4 more Smart Citations
“…Ali et al showed in their study an overall higher protein expression in early-stage OA and a reduced response in late-stage OA [ 13 ].…”
Section: Synovial Fluid Physiopathologymentioning
confidence: 99%
“…Cartilage intermediate layer protein 1 (CILP) is a matrix protein that resides in the human articular cartilage and is involved in numerous diseases that affect cartilage. Its overexpression may lead to impaired chondrocyte growth and matrix repair [ 13 , 14 , 15 , 16 ]. Specifically, CILP has a relevant role in regulating the metabolism of the extracellular matrix (ECM).…”
Section: Synovial Proteomic Biomarkers In Oamentioning
confidence: 99%
See 3 more Smart Citations